P537 The impact of early disease control with vedolizumab on surgery rates among patients with Crohn's disease: a post-hoc analysis of the GEMINI trials. (25th January 2019) - Dulai, P; Peyrin-Biroulet, L; Hahn, K; Khalife, N; Lindner, D; Lasch, K; Demuth, D; Patel, H; Jairath, V
Abstract: Background: In Crohn's disease (CD), short disease duration is associated with greater response to anti-tumour necrosis factor α therapy. The impact of disease duration on surgery rates in vedolizumab-treated patients with CD has not been established. A clinical decision support tool (CDST) was developed using data from the GEMINI 2 trial and validated with data from the VICTORY consortium to predict clinical and endoscopic remission with vedolizumab in CD. 1 Whether earlier treatment with vedolizumab reduced the risk of CD-related surgery in patients with low, intermediate, or high probability of response to vedolizumab was assessed. Methods: Individual patient data from GEMINI 2 and the open-label GEMINI long-term safety studies were evaluated. Early and late disease were defined as ≤2 vs. >2, ≤3 vs. >3, and ≤5 vs. >5 years of disease duration. CD-related surgery was defined as bowel resection and colectomy. Patients were stratified according to the CDST into low, intermediate, or high probability of response to vedolizumab, and logistic regression and Cox-proportional hazard analyses were used to assess the impact of early disease intervention with vedolizumab in these subgroups. Odds ratios (ORs) with 95% confidence intervals (CIs) are reported. Results: A combined total of 1253 patients with CD from the GEMINI studies were included (mean [SD] age, 36.4 [12.4] years; 55.1% female), with 113 (9.0%) requiring CD-related surgery during the 7-year follow-up period. Surgical rates were 12.9%, 8.1%, and 6.0% for the low, intermediate, and high probability of vedolizumab response groups based on the CDST. Patients with low probability of response had a 2-fold (hazard ratio, 2.32; 95% CI, 1.29–4.30) increased risk of surgery while receiving vedolizumab relative to the high probability of response group. Overall, there was a trend of lower rates of CD-related surgery among patients treated earlier in their disease course (table). For the low probability of vedolizumab response group, patients with CD with a disease duration of ≤5 years had 39% lower odds of requiring CD-related surgery compared with patients with disease duration >5 years (OR, 0.61; 95% CI, 0.36–0.99). Conclusions: This post hoc analysis suggests that treatment of patients with CD with vedolizumab earlier in their disease course is associated with lower rates of surgery up to a 7-year time horizon, regardless of baseline probability of response to vedolizumab. Reference 1. Dulai PS, Boland BS, Singh S et al. Development and validation of a scoring system to predict outcomes of vedolizumab treatment in patients with Crohn's disease. Gastroenterology 2018;155:687–695.e10.